Hemicraniectomy for Geriatric Stroke Patients Affects Disposition Following Discharge. (16th November 2020) - Wu, Adela; Jin, Michael C; Rodrigues, Adrian; Li, Gordon
Abstract: INTRODUCTION: Ischemic stroke disproportionately affects older individuals (1440701 [Wolf et al], 16298214 [Rothwell et al]). Malignant edema as a result of large territory ischemic stroke causes imminent and life-threatening brain compression, which may be alleviated by early decompressive hemicraniectomy, which has been shown to provide favorable survival and functional outcomes for stroke patients. METHODS: Patients admitted with ischemic stroke receiving hemicraniectomy (CPT: 61322) between 2004 and 2017 were identified from the Optum Clinformatics Data Mart Claims Database. Early hemicraniectomy was considered <72 hours from last known normal. Primary outcomes of interest were inpatient mortality and discharge outcomes. Discharge to home or short-term care was considered a positive outcome. Secondary outcomes include duration of post-surgical stay, post-discharge readmissions, and post-discharge mortality. RESULTS: Our cohort included 447 patients, of which a total of 369 patients (82.6%) underwent early hemicraniectomy within 72 hours of stroke onset and a total of 157 patients (42.5%) were over 60 years of age. Average age of patients in both early and late hemicraniectomy groups was similar (55.8 years versus 56.4 years, P = .709). Geriatric patients are at increased risk of passing while hospitalized (OR 2.095, 95% CI 1.378-3.185, P = .001). Overall, older patients also have low odds of achieving positive discharge outcomes to either home or short-term care facilities (OR 0.279, 95% CI 0.179-0.435, P < .001). Age over 60 was significantly associated with readmission (HR 1.487, 95% 1.077-2.054, P = .016). For the cohort, late hemicraniectomy was related to lower odds of positive discharge outcomes (OR 0.505, 95% CI 0.284-0.896, P = .020). CONCLUSION: Early decompressive hemicraniectomy has been repeatedly shown to have survival and functional benefit for patients with large-territory ischemic stroke and malignant edema. Using a national database containing information on both inpatient and outpatient data, we found that the geriatric subset of these patients have high risk for poor outcomes during their hospitalizations as well as post-discharge.